2000
DOI: 10.1029/2000wr900128
|View full text |Cite
|
Sign up to set email alerts
|

Soil gas transport above a jet fuel/solvent spill at Plattsburgh Air Force Base

Abstract: Abstract. We calibrate a stoichiometrically coupled soil gas diffusion model with spatially resolved observations of oxygen, carbon dioxide, total hydrocarbon, and trichloroethylene vapor concentrations in the unsaturated zone above a weathered jet fuel/solvent spill at Plattsburgh Air Force Base in upstate New York. The calibration suggests that aerobic microorganisms in the capillary fringe degrade jet fuel vapor at a steady rate of 9.5 hydrocarbons (m -2 s-l). The solvent does not degrade in the fringe, how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…Pasteris et al (2002) found that aerobic biodegradation of the petroleum vapors was the primary mechanism that limited migration away from the NAPL source, and that this biodegradation accounted for most of the mass loss from the experimental system. MTBE, which was not found to biodegrade under these controlled conditions, was the only compound detected in groundwater 1.2 m below the Downloaded by [Simon Fraser University] at 05:09 19 November 2014 Ostendorf et al (2000) found similar results at a spill site with a mixed petroleum and trichloroethylene (TCE) LNAPL source present at the water table at Plattsburgh AFB in upstate New York. Ostendorf et al (2000) found that the diffusive flux of oxygen from the ground surface was sufficient to support essentially complete biodegradation of all petroleum VOCs evaporating from the LNAPL source.…”
Section: Observed Differences In Hydrocarbon and Chlorinated Voc Vaposupporting
confidence: 80%
See 1 more Smart Citation
“…Pasteris et al (2002) found that aerobic biodegradation of the petroleum vapors was the primary mechanism that limited migration away from the NAPL source, and that this biodegradation accounted for most of the mass loss from the experimental system. MTBE, which was not found to biodegrade under these controlled conditions, was the only compound detected in groundwater 1.2 m below the Downloaded by [Simon Fraser University] at 05:09 19 November 2014 Ostendorf et al (2000) found similar results at a spill site with a mixed petroleum and trichloroethylene (TCE) LNAPL source present at the water table at Plattsburgh AFB in upstate New York. Ostendorf et al (2000) found that the diffusive flux of oxygen from the ground surface was sufficient to support essentially complete biodegradation of all petroleum VOCs evaporating from the LNAPL source.…”
Section: Observed Differences In Hydrocarbon and Chlorinated Voc Vaposupporting
confidence: 80%
“…MTBE, which was not found to biodegrade under these controlled conditions, was the only compound detected in groundwater 1.2 m below the Downloaded by [Simon Fraser University] at 05:09 19 November 2014 Ostendorf et al (2000) found similar results at a spill site with a mixed petroleum and trichloroethylene (TCE) LNAPL source present at the water table at Plattsburgh AFB in upstate New York. Ostendorf et al (2000) found that the diffusive flux of oxygen from the ground surface was sufficient to support essentially complete biodegradation of all petroleum VOCs evaporating from the LNAPL source. This biodegradation occurred in close proximity to the capillary fringe and resulted in production of carbon dioxide at a rate that stoichiometrically matched the estimated evaporation rate for the petroleum VOCs from the LNAPL.…”
Section: Observed Differences In Hydrocarbon and Chlorinated Voc Vaposupporting
confidence: 80%
“…Ostendorf and Kampbell (1991) concluded that aerobic biodegradation of hydrocarbon vapours in the unsaturated zone prevents the escape of appreciable contamination to the atmosphere from an aviation gasoline spill. Moreover, Ostendorf et al (2000) observed that aerobic microorganisms in the subsurface degrade jet fuel vapour and nearly all of the evaporating jet fuel is consumed in the contaminated capillary fringe. Additionally, Lahvis et al (1999) underscored the importance of aerobic biodegradation in limiting the transport of hydrocarbon vapours in the unsaturated zone and implied that vapour-plume migration into basements and other points of contact may only be significant if a source of the free product is present.…”
Section: Introductionmentioning
confidence: 97%
“…In the steady‐state methods, one‐dimensional gas diffusion models based on Fick’s law are calibrated against measured CO 2 (De Jong & Schappert, 1972; Osozawa & Hasegawa, 1995; Hashimoto & Suzuki, 2002) or O 2 and CO 2 concentration versus depth data (Ostendorf et al , 2000) to predict soil respiration. Kerfoot (1994) discussed the use of both O 2 and CO 2 concentration gradients measured in situ to determine the degradation rate of saturated‐zone hydrocarbon contamination.…”
Section: Introductionmentioning
confidence: 99%
“…Time‐averaged concentrations of hydrocarbon vapours and O 2 were used to calibrate the model by estimating the hydrocarbon degradation rate, described by two parameters, namely the maximum reaction rate, V , and the half‐saturation constant, K . Another stoichiometrically coupled soil gas diffusion model was developed by Ostendorf et al (2000). They used concentration data and a set of steady‐state and transient one‐dimensional, analytical transport models to estimate the flux of soil gas constituents through a uniform, permeable, unsaturated zone.…”
Section: Introductionmentioning
confidence: 99%